2019
DOI: 10.1007/s13730-019-00397-1
|View full text |Cite
|
Sign up to set email alerts
|

A relapsing case of pulmonary–renal syndrome after a sequential rise in MPO–ANCA and anti-GBM antibodies

Abstract: A 69-year-old woman who presented with severe renal dysfunction and diffuse alveolar hemorrhage was diagnosed with pulmonary-renal syndrome (PRS) based on the coexistence of serum myeloperoxidase (MPO)-antineutrophil cytoplasmic antibodies (ANCA) and anti-glomerular basement membrane (GBM) antibodies (Ab). Hemodialysis was started; plasma exchange and intravenous methylprednisolone pulse therapy were administered followed by oral prednisolone administration. Pulmonary hemorrhage decreased; however, renal dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The scientific community had put forward many hypotheses about the two antibodies, although the mechanism of action between them has not been clearly studied. Several studies suggested that AAV might develop first following its natural disease history, and then anti-GBM antibodies could emerge with corresponding clinical manifestation (15)(16)(17)(18). It warrants further study to explore the differences between isolated MPO-ANCA or anti-GBM positive and double positive types, including original serological, immunological, pathological and prognostic index.…”
Section: Discussionmentioning
confidence: 98%
“…The scientific community had put forward many hypotheses about the two antibodies, although the mechanism of action between them has not been clearly studied. Several studies suggested that AAV might develop first following its natural disease history, and then anti-GBM antibodies could emerge with corresponding clinical manifestation (15)(16)(17)(18). It warrants further study to explore the differences between isolated MPO-ANCA or anti-GBM positive and double positive types, including original serological, immunological, pathological and prognostic index.…”
Section: Discussionmentioning
confidence: 98%